Higher mortality rates for large‐ and medium‐sized mammals on plantation roads compared to highways in Peninsular Malaysia. Issue 21 (16th October 2020) - Jamhuri, Jamaluddin; Edinoor, Mohd Anuar; Kamarudin, Norizah; Lechner, Alex M.; Ashton‐Butt, Adham; Azhar, Badrul
Abstract: The fragmentation of forests by agricultural expansion, urbanization, and road networks is an ongoing global biodiversity crisis. In Southeast Asia and other tropical regions, wildlife populations are being isolated into pockets of natural habitat surrounded by road networks and monoculture plantations. Mortality from wildlife–vehicle collisions (WVCs) is contributing to a decline in many species of conservation priority in human‐modified landscapes. This study is the first in Malaysia to investigate factors affecting the occurrence of WVCs. We assessed roadkill data gathered by the Department of Wildlife and National Parks on small‐, medium‐, and large‐sized mammals in Peninsular Malaysia. We examined the relationship between wildlife road accidents and several environmental factors. We found a total of 605 roadkill animals, involving 21 species, which included three species classified as Endangered. Road type (plantation road or highway), year, and distance of the road from continuous and fragmented forests were significant in determining mammal mortality. Unexpectedly, the majority of road mortality occurred on palm oil plantation roads compared to highways. Mortality of small‐ and medium‐sized mammals was greater at locations further from continuous forest than those closer to fragmented forests. Segmentation of continuous forest by roads should be avoided wherever possible to reduce the threat of roads on crossing wildlife. Abstract : Wildlife populations are being isolated into forest patches surrounded by roads. The majority of road mortality occurred on plantation roads compared to highways. Road type, altitude, and distance from forest were major drivers of mortality.